2014
DOI: 10.1186/1471-2431-14-231
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the prevalence of parental concerns measured by the Parents’ Evaluation of Developmental Status (PEDS)indicating developmental risk

Abstract: BackgroundParental concerns about their children’s development can be used as an indicator of developmental risk. We undertook a systematic review of the prevalence of parents’ concerns as an indicator of developmental risk, measured by the Parents’ Evaluation of Developmental Status (PEDS) and associated risk factors.MethodsElectronic databases, bibliographies and websites were searched and experts contacted. Studies were screened for eligibility and study characteristics were extracted independently by two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 50 publications
6
81
5
Order By: Relevance
“…One previous review suggested that parenting concerns are closely related to outcomes and that the concerns of parents and teachers are likely to be an effective first screening tool for children at developmental risk, if stigma can be reduced [7]. This study further highlights the need to develop a new screening system that utilizes the perceptions of parents and multidisciplinary professionals who traditionally have not played a major role in mass screening systems of children with any healthcare needs in Japan.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…One previous review suggested that parenting concerns are closely related to outcomes and that the concerns of parents and teachers are likely to be an effective first screening tool for children at developmental risk, if stigma can be reduced [7]. This study further highlights the need to develop a new screening system that utilizes the perceptions of parents and multidisciplinary professionals who traditionally have not played a major role in mass screening systems of children with any healthcare needs in Japan.…”
Section: Discussionmentioning
confidence: 81%
“…Globally, it is known that children with these developmental difficulties often go undiagnosed and are thus deprived of the opportunity for early intervention [3, 4, 6]. Moreover, the developmental outcome for these children is associated with psychosocial factors such as socioeconomic status and maternal mental health, as well as access to and compliance with treatment [6, 7]. Therefore, in many areas around the globe, it is now recommended to provide early intervention for a wide range of children who are considered at risk of developing behavioral and emotional disorders, to prevent future social exclusion as well as their parents’ difficulties (for example in Australia and Sweden [8, 9]).…”
Section: Introductionmentioning
confidence: 99%
“…9 In contrast, a study conducted on a global scale, including data from 11 countries, depicted a lower referral rate of 34%. 24 The high referral rate noted in the abovementioned South African contexts may be problematic as the already overburdened healthcare system may not be able to provide effective and accountable services to all, should developmental screening be implemented on a large scale. The PEDS tool referral algorithm may need to be adapted for the South African underserved population to ensure that moderate to severe developmental delays are detected, as well as referred, and that mild developmental delays are followed up by means of developmental surveillance.…”
Section: Discussionmentioning
confidence: 97%
“…Parental concerns have long been shown to accurately predict the presence of developmental issues and disabling conditions . Taking the time to ensure that families’ concerns are fully elicited and addressed within the consultation can help families to feel more in control of health care .…”
Section: Discussionmentioning
confidence: 99%